Protection of Photosynthesis by Halotolerant Staphylococcus sciuri ET101 in Tomato (Lycoperiscon esculentum) and Rice (Oryza sativa) Plants During Salinity Stress: Possible Interplay Between Carboxylation and Oxygenation in Stress Mitigation - Taj, Zarin; Challabathula, Dinakar (Frontiers in Microbiology, 2021)
Tomato (Lycoperiscon esculentum) and rice (Oryza sativa) are the two most important agricultural crops whose productivity is severely impacted by salinity stress. Soil salinity causes an irreversible damage to the photosynthetic apparatus in plants at all developmental stages leading to significant reduction in agricultural productivity. Reduction in photosynthesis is the primary response that is observed in all glycophytic plants during salt stress. Employment of salt-tolerant plant growth promoting bacteria (PGPB) is economical and viable approach for the remediation of saline soils and improvement of plant growth. The current study is aimed towards investigating the growth patterns and photosynthetic responses of rice and tomato plants upon inoculation with halotolerant PGPB Staphylococcus sciuri ET101 under salt stress conditions. Tomato and rice plants inoculated with PGPB showed increased growth rate, stimulated root growth, along with higher transpiration rates (E), stomatal conductance (gs) and intracellular CO2 accumulation (Ci). Additionally, correlation of relative water content to electrolyte leakage in tomato and rice plants showed decreased electrolyte leakage in inoculated plants during salt stress conditions along with higher proline and glycine betaine content. Energy dissipation by non-photochemical quenching (NPQ) and increased photorespiration of 179.47% in tomato and 264.14% in rice plants were observed in uninoculated plants subjected to salinity stress. Furthermore, reduced photorespiration with improved salinity tolerance is observed in inoculated plants. The higher rates of photosynthesis in inoculated plants during salt stress were accompanied by increased quantum efficiency (ΦPSII) and maximum quantum yield (Fv/Fm) of photosystem II. Furthermore, inoculated plants showed increased carboxylation efficiency of RuBisCO along with higher photosynthetic electron transport rate (J) during salinity stress. Although the total cellular ATP levels are drastically affected by salt stress in tomato and rice plants along with increased ROS accumulation, the restoration of cellular ATP levels in leaves of inoculated plants along with decreased ROS accumulation suggests the protective role of PGPB. Our results reveal the beneficial role of Staphylococcus sciuri ET101 in protection of photosynthesis and amelioration of salinity stress responses in rice and tomato plants.